"Are You Doing What I Think You're Doing?" Momentary Goal Projection and Goal Contagion in Romantic Conflict. (February 2023) - Worley, Timothy; Vanderbilt, Rachel; Liu, Esther
This study examined how individuals' goals and inferences about partners' goals vary moment-by-moment during romantic conflicts. Seventy romantic couples discussed a current relational conflict for 7 minutes. Participants individually reviewed video recordings of their discussion, rating the importance of their own goals and inferences about the importance of those goals for their partner during each minute. Individuals demonstrated mixed accuracy when inferring partners' goals. We observed evidence of goal projection, as the more important a goal was to oneself, the more one inferred it was important to the partner. We also observed evidence of goal contagion, as inferences about a partner's goals mediated several associations between the partner's previous goals and individuals' subsequent goals. Furthermore, inferences about partners' goals also mediated associations between individuals' own prior goals and their goals at the next minute.